THE BEGINNINGS OF SPIRITUAL AUTOBIOGRAPHY - 2 CORINTHIANS 12, 2-5 : A HERMENEUTICAL APPROACH - Morariu, Iuliu-Marius (Journal of Education Culture and Society, 2020)
Aim/Thesis. In this inquiry, the author examines the 12th chapter of the 2nd letter of Paul to the Corinthians in a hermeneutical way, highlighting its relevance for a Christian’s spiritual autobiography and emphasizing the influence it has had on the later development of the genre. Concept/Methods. Using patristic exegesis (like that of Saint Chrysostom)t and also that of more recent authors dedicated to this theme, he tries not only to present and explain the event, but also to offer new interpretive keys for reading it. Results and conclusion. The approach focuses on keywords and phrases like "the rapture", "glimpse" or "thorn in the flesh" and it tries to presents Paul’s understanding of the link between the spiritual experience of encountering God and the suffering that follows it, as a useful means of humbling a person. The research also highlights some important examples that show how the Apostle influenced the style and the way of thinking of later authors like Saint Augustine or Saint Silouan from Mount Athos. Originality/Cognitive value. The relevance of showing why Saint Paul’s second letter to Corinthians (12, 2-) represents the beginning of the spiritual autobiography in the Christian space is a very big one due to the fact it can helps the reader to have a deeper understanding of latter spiritual autobiographies like the one of Saint Siluan, father John of Kronstadt, Teresa of Calcutta or Maria Faustina Kowalska.